2010
DOI: 10.1038/ki.2009.473
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly glycosylated IgA1 induces mesangial cells to produce platelet-activating factor that mediates nephrin loss in cultured podocytes

Abstract: The reaction of mesangial cells with aberrantly glycosylated IgA1 has been implicated in the etiology of IgA nephropathy (IgAN). Tumor necrosis factor, which is assumed to mediate the interaction between mesangial cells and podocytes, also induces the expression of platelet-activating factor (PAF). In this study, we determined whether PAF affects the expression of nephrin (an adhesion molecule critical to glomerular permselectivity) and cytoskeletal F-actin organization in podocytes. We treated human mesangial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Mesangial cell-derived mediators induce proliferation of proximal tubular epithelial cells and synthesis of inflammatory mediators (29). Moreover, mesangial cell-derived TNF-a and plateletactivating factor downregulate podocyte markers, resulting in altered glomerular permeability and enhanced proteinuria in IgAN (30,31). These data indicate that such mediators play an important role in the cross-talk between the different cell types present in glomeruli.…”
Section: Discussionmentioning
confidence: 73%
“…Mesangial cell-derived mediators induce proliferation of proximal tubular epithelial cells and synthesis of inflammatory mediators (29). Moreover, mesangial cell-derived TNF-a and plateletactivating factor downregulate podocyte markers, resulting in altered glomerular permeability and enhanced proteinuria in IgAN (30,31). These data indicate that such mediators play an important role in the cross-talk between the different cell types present in glomeruli.…”
Section: Discussionmentioning
confidence: 73%
“…Recently the molecular distribution of lipids was analyzed in hyper-IgA murine kidneys using MALDI-quadrupole ion trap-TOF-based imaging MS [133]. [134,135]. This study also indicated that all the hyper-IgA-specific lipids were derived from urine and that stagnation due to unilateral urethral obstruction caused hyper-IgA-specific distribution of lipids in renal tubules.…”
Section: Lipidomics In Animal Models or Cell Modelsmentioning
confidence: 88%
“…Based on the physical and biologic characteristics of the immune complexes, such as composition and size, 17,28 mesangial cells may be activated to proliferate and overproduce components of mesangial matrix, chemokines, and cytokines. 29,30 Overall, the serum levels of normalized IgG autoantibody and total IgA autoantibody steadily increased with the ARR level (ARR=3 . ARR=2 .…”
Section: Discussionmentioning
confidence: 99%